Comparison of Three-Dimensional Speckle Tracking Echocardiography and Two-Dimensional Echocardiography for Evaluation of Left Atrial Size and Function in Healthy Volunteers (Results from the MAGYAR-Healthy Study) - Nemes, Attila; Domsik, Péter; Kalapos, Anita; Lengyel, Csaba; Orosz, Andrea; Forster, Tamás (Echocardiography (Mount Kisco, N.Y.), 2014)
Objective Noninvasive accurate assessment of left atrial (LA) size and function is an essential requirement in daily clinical practice. Real time three‐dimensional (3D) echocardiography (RT3DE) with direct volumetric method has been found to be a highly accurate and reproducible noninvasive tool for the evaluation of LA dimensions and functional properties. Three‐dimensional speckle tracking echocardiography (3DSTE) has just been introduced for volumetric assessments, which uses different, as called “block‐matching” algorithm by strain analysis. This study was designed to compare two‐dimensional (2D) echocardiography with 3DSTE for calculation of LA volumes and assessment of LA functional properties in healthy subjects. Methods This study comprised of randomly selected 35 healthy subjects (40.9 ± 10.9 years, 20 men) in sinus rhythm, they all had undergone standard transthoracic 2D echocardiographic Doppler study extended with 3DSTE. Results Two‐dimensional echocardiography– and 3DSTE‐derived minimum (Vmin) and maximum (Vmax) LA volumes and LA volume before atrial contraction (Vpre A) did not differ significantly. Calculated functional LA properties were also compared. Good correlations were found between both techniques for Vmax (r = 0.93, P < 0.0001), Vmin (r = 0.62, P < 0.0001), and Vpre A (r = 0.74, P < 0.0001). Conclusions It may be stated that 3DSTE seems to be feasible in detection of cyclic changes in LA volumes and calculation of its functional properties is comparable to 2D echocardiography.